Factors Affecting the Banking Service Quality in Vietnam - Phan Dien Vy; Phan Thanh Tam (International Journal of Supply Chain Management, 2021)
In the current fierce competition between banks, increasing service quality is considered the foundation of the banks’ competitive strategy to attract and retain customers. Therefore, the research and analysis of the factors of banking service-affecting banking service quality are essential. The article assesses the influence of the aspects of banking service quality. Besides, this study objective tested the reliability of the banking service quality of commercial banks in Vietnam. The study surveyed 1.000 customers related to commercial banks, but 917 samples processed and answered 39 questions. The data collected from July 2020 to December 2020. The authors tested Cronbach’s Alpha, confirmatory factor analysis (CFA), and structural equation model (SEM) for factors affecting the banking service quality of commercial banks in Vietnam with a significance level of 0.01